2011
DOI: 10.1021/ie102596c
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Crystallization of Macromolecules using Patterned Substrates in a Sandwiched Plate Geometry

Abstract: Crystallization of macromolecules such as proteins and peptides is known to be influenced by the topographical and chemical heterogeneity of the substrate. However, controlling the nucleation and the growth of crystal on such surfaces has been an issue. Here, we present systematic experiments carried out on hydrophilic elastomeric substrates topographically patterned by forming stretch induced surface wrinkles; the distance between the wrinkles, importantly the density of occurrence of defects between the wrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In the case of PI ( 20 – 25 ) and sPEEK-WC ( 15 – 16 ), the opposite tendency was observed for the three target molecules, although the influence of PI surfaces topography on nucleation rate of ACM was only slightly evident, due to reduced interaction with this polymer. In this case, increased surface roughness supported the nucleation rate as also reported by some authors. ,, Observations of co-PVDF and PP samples substantiate instead those results demonstrating the inefficacy, or even the reduction, of the nucleation activity of a solid support in some circumstances when increasing roughness. ,,, The opposite effect of surface roughness on the nucleation activity for intrinsically hydrophobic and more hydrophilic polymer surfaces, correlates well with the wetting behavior of the different polymeric templates by the crystallizing solutions, as demonstrated by static contact angles θ ACM , θ ASA , and θ GLY (right-hand axes in Figure ). Results show that wetting behavior of the surface dictates whether enhanced roughness would positively affect nucleation rate, in accordance with classical nucleation theory (CNT), and explain the different impact of roughening on nucleation density displayed in Figure .…”
Section: Resultssupporting
confidence: 85%
“…In the case of PI ( 20 – 25 ) and sPEEK-WC ( 15 – 16 ), the opposite tendency was observed for the three target molecules, although the influence of PI surfaces topography on nucleation rate of ACM was only slightly evident, due to reduced interaction with this polymer. In this case, increased surface roughness supported the nucleation rate as also reported by some authors. ,, Observations of co-PVDF and PP samples substantiate instead those results demonstrating the inefficacy, or even the reduction, of the nucleation activity of a solid support in some circumstances when increasing roughness. ,,, The opposite effect of surface roughness on the nucleation activity for intrinsically hydrophobic and more hydrophilic polymer surfaces, correlates well with the wetting behavior of the different polymeric templates by the crystallizing solutions, as demonstrated by static contact angles θ ACM , θ ASA , and θ GLY (right-hand axes in Figure ). Results show that wetting behavior of the surface dictates whether enhanced roughness would positively affect nucleation rate, in accordance with classical nucleation theory (CNT), and explain the different impact of roughening on nucleation density displayed in Figure .…”
Section: Resultssupporting
confidence: 85%
“…The atomic force microscopy (AFM) images show the profile of PDMS films at the vicinity of an incision. Images (a-c) correspond to a PDMS film without any surface modification (set I type of substrate), one plasma oxidized for 4 min (set II type) and one (set III type) consisting of nano-to microscopic wrinkles prepared by the method described in [12]. (d-f) Images represent 3D plots of surfaces corresponding to those in images a-c, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, features having a large range in sizes have the advantage that they can induce nucleation of protein molecules of different sizes. Such substrates are designated as universal nucleant [11][12][13][14][15], the large standard deviation in feature size of which has been shown to diminish the energy barrier for nucleation [11]. Not only the size of surface features, but also their shape has been found to influence crystal nucleation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Reports indicate that the mechanism of protein crystallization is affected by the depth of the microchannel 15 and the nature of the solid surface. [16][17][18][19] In the previous report, we demonstrated that the volume and shape of the nanodroplet influence the protein crystallization behaviour, i.e. the number of crystals and the induction time.…”
Section: Introductionmentioning
confidence: 94%